Utilization of Yellow Sweet Potato Flour in Pumpkin Puree Pie to Increase Beta-carotene Content: Pemanfaatan Tepung Ubi Jalar Kuning Pada Pie Puree Labu Kuning Untuk Meningkatkan Kadar Beta-karoten - Iswahyudi; Nurul Karima, Rafika; Mira Sofyaningsih (Jurnal Pangan dan Agroindustri, 2026)
Abstract The objective of the study was to analyze the effect of different formulations utilizing yellow sweet potato flour and yellow pumpkin puree on the beta-carotene content and organoleptic characteristics of the pie. The study employed a Completely Randomized Design, with the treatment factor being the variation in formulation due to the substitution of yellow sweet potato flour and yellow pumpkin puree in each pie formula. The variables tested included beta-carotene content, organoleptic tests conducted by 50 untrained panelists, and proximate analysis only for the selected formula. Data were analyzed using an independent sample t-test, ANOVA, Kruskal-Wallis test, and follow-up Mann-Whitney test (with a 95% significance level). The results showed that the use of yellow sweet potato flour did not have a significant effect on moisture, fat, carbohydrate, and beta-carotene content (p > 0.05). The organoleptic test results indicated a significant effect on color and texture parameters (p < 0.05). The selected pie formulation was F2 (containing 40% yellow sweet potato flour), which had a beta-carotene content of 2672 mcg.   Abstrak Tujuan penelitian yaitu menganalisis pengaruh perbedaan formulasi yang memanfaatkan tepung ubi jalar kuning dan puree labu kuning terhadap kadar beta-karoten dan karakteristik organoleptik pie. Penelitian menggunakan Rancangan Acak Lengkap dengan perbedaan formulasi yang disebabkan oleh substitusi tepung ubi jalar kuning dan puree labu kuning pada setiap formula pie menjadi faktor perlakuan. Variabel yang diuji meliputi kadar betakaroten, uji organoleptik menggunakan 50 panelis tidak terlatih, dan kadar proksimat hanya pada formula terpilih. Data dianalisis menggunakan uji independent sample t-test, ANOVA dan uji Krusskal-Wallis serta uji lanjut Mann-Whitney (signifikan 95%). Hasil penelitian menunjukkan bahwa penggunaan tepung ubi jalar kuning tidak memberikan pengaruh nyata terhadap kadar air, lemak, karbohidrat, dan beta-karoten (p > 0,05). Hasil uji organoleptik menunjukkan terdapat pengaruh nyata terhadap parameter warna dan tekstur (p < 0,05). Formulasi pie terpilih yaitu F2 (tepung ubi jalar kuning sebanyak 40%), memiliki 2672 mcg beta-karoten.